2012
DOI: 10.1089/scd.2011.0370
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Characterization of Embryonic Stem Cells Lines Derived from Transgenic Fischer 344 and Dark Agouti Rats

Abstract: Rat embryonic stem cell (ESC) lines are not widely available, and there are only 2 lines available for distribution. Here, ESC lines were derived and characterized from Fischer 344 (F344) rats that express marker transgenes either b-galactosidase or human placental alkaline phosphatase (AP), nontransgenic F344 rats, and from Dark Agouti (DA) rats. The ESC lines were maintained in an undifferentiated state as characterized by colony morphology, expression of Oct4, Nanog, Sox-2, Cdx2, and Stella, staining for AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 36 publications
(63 reference statements)
1
24
0
Order By: Relevance
“…The differences that exist between human and rat ESCs or between rat and mouse ESCs are yet to be fully elucidated. For example, we recently reported that rat ESCs maintained using the 2 inhibitor cocktail of PD0325901, a mitogen-activated protein kinase (MEK) inhibitor, and CHIR99021, a glycogen synthase kinase 3 (GSK3) inhibitor plus leukemia inhibitory factor (LIF), called two inhibitors (2i) below, express Cdx2 [6], a gene involved in trophoblast fate determination [7,8]. This finding is in sharp contrast to what is observed in mouse ESCs.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…The differences that exist between human and rat ESCs or between rat and mouse ESCs are yet to be fully elucidated. For example, we recently reported that rat ESCs maintained using the 2 inhibitor cocktail of PD0325901, a mitogen-activated protein kinase (MEK) inhibitor, and CHIR99021, a glycogen synthase kinase 3 (GSK3) inhibitor plus leukemia inhibitory factor (LIF), called two inhibitors (2i) below, express Cdx2 [6], a gene involved in trophoblast fate determination [7,8]. This finding is in sharp contrast to what is observed in mouse ESCs.…”
Section: Introductionmentioning
confidence: 92%
“…Rat ESC lines used here were derived from Dark Agouti (DA) and transgenic Fischer 344 (F344) rats. ESC derivation, ESC differentiation to embryoid bodies (EBs), and characterization of our DA and F344 ESCs was described previously [6]. In addition, 2i plus LIF genuine rat ESC pellets derived from DA rats were provided by Dr. Q. Ying (University of Southern California, Los Angeles, CA) [4].…”
Section: Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…While a number of groups have derived ES cell lines and generated chimeras, it is clear that several lines then failed to demonstrate germline transmissibility [20,21]. Several factors, such as the genetic background, stemness, normality of karyotype, pathogen status of the ES cell line, as well as the genetic background of recipient embryos, affect the ES cells' ability to transmit their genetic material through the germline [13,14].…”
Section: Discussionmentioning
confidence: 99%